Mechanism of Passive Layer Formation on AA2024-T3 from Alkaline Lithium Carbonate Solutions in the Presence of Sodium Chloride. Issue 2 (1st January 2018) - Visser, Peter; Gonzalez-Garcia, Yaiza; Mol, Johannes M. C.; Terryn, Herman
Abstract : This study focuses on the elucidation of the formation mechanism of passive layers on AA2024-T3 during the exposure to alkaline lithium carbonate solutions in the presence of sodium chloride. Under controlled conditions, in an electrochemical cell, a protective layer was generated comprising an amorphous inner layer and a crystalline outer-layer. In order to resolve the formation mechanism, the layers were characterized using surface analytical techniques to characterize the surface morphology, thickness and elemental composition of the layers at different stages of the formation process. In addition, electrochemical techniques were applied to link the electrochemical properties of the layers with the different stages of formation. The results demonstrate that the formation mechanism of these layers comprises three different stages: (I) oxide thinning, (II) anodic dissolution and film formation, followed by (III) film growth through a competitive growth-dissolution process. The passive properties of the layers are generated in the third stage through the densification of the amorphous layer. The combined results provide an enhanced insight in the formation mechanism and the development of the passive properties of these layers when lithium salts are used as leaching corrosion inhibitor for coated AA2024-T3.